Energetic Charged Particle Fluxes Relevant to Ganymede's Polar Region. Issue 23 (12th December 2022) - Paranicas, C.; Mauk, B. H.; Kollmann, P.; Clark, G.; Haggerty, D. K.; Westlake, J.; Liuzzo, L.; Masters, A.; Cassidy, T. A.; Bagenal, F.; Bolton, S.
Abstract: The JEDI instrument made measurements of energetic charged particles near Ganymede during a close encounter with that moon. Here we find ion flux levels are similar close to Ganymede itself but outside its magnetosphere and on near wake and open field lines. But energetic electron flux levels are more than a factor of 2 lower on polar and near‐wake field lines than on nearby Jovian field lines at all energies reported here. Flux levels are relevant to the weathering of the surface, particularly processes that affect the distribution of ice, since surface brightness has been linked to the open‐closed field line boundary. For this reason, we estimate the sputtering rates expected in the polar regions due to energetic heavy ions. Other rates, such as those related to radiolysis by plasma and particles that can reach the surface, need to be added to complete the picture of charged particle weathering. Plain Language Summary: This paper uses Juno data to quantify the levels of energetic charged particle flux near Jupiter's moon Ganymede. We have computed energy spectra (energy vs. charged particle intensity) for electrons, protons, oxygen and sulfur ions, from a near encounter of Ganymede by the Juno spacecraft in June 2021. Particle fluxes may be important for weathering processes on Ganymede, such as the sputtering of water ice in the top layer. The distribution of water ice in the upper layer of Ganymede's surface does not appear to be consistent with sublimation alone, so questions remain about which processes are dominant in shaping the ice distribution. Quantification of the flux levels is also needed for planning, for example, for ESA's JUICE mission, expected to orbit Ganymede in the future. Key Points: We present energy spectra from energetic charged particle data from Juno's close flyby of Ganymede in 2021 We find a drop in electron fluxes on polar field lines compared to the surrounding region whereas ion fluxes are similar in both regions We compute sputtering rates to evaluate particle weathering, as a step toward understanding the distribution of Ganymede's surface ice